The Practice of Body Power and Masculine Resistance of Male Actors in Indonesian Comedy Films of the Reform Era - Aminudin, Amin; Ana Nadhya Abrar; Novi Kurnia (CV. AFDIFAL MAJU BERKAH, 2024)
The practice of power over male actors' bodies in comedy films is understood not as a neutral process where factual reality is conveyed directly through text or images, but as a social praxis related to the deconstruction of gender, resulting in new understandings of masculinity depicted in films from the Reform Era. To address this question, the researcher employs Norman Fairclough's critical discourse approach to comedy films as the main theoretical framework, combined with Michel Foucault's perspective on power relations and Maurice Merleau-Ponty's theory of body language. The paradigm used in this research is the critical paradigm, with data collection techniques obtained through film text documentation studies. The research results show that the male actor's body does not merely function as a tool for visual narration but also as a powerful medium for expressing deeper themes related to power, identity, and social dynamics. For instance, in the film Arisan! 2, the narrative highlights sexual freedom and emotional vulnerability. Meanwhile, Bebas emphasizes physical changes and social symbolism through the male body.